External 3PE and internal epoxy resin anti-corrosion pipeline and production process thereof

By using low molecular weight bisphenol A epoxy resin and 2-methylimidazolium-propylmaleic anhydride curing agent, combined with silanized nanoparticle treatment, the problem of insufficient leveling performance of epoxy powder coating in 3PE anti-corrosion technology was solved, and the bonding strength and cathodic disbondment resistance of the anti-corrosion layer were improved.

CN121017066AActive Publication Date: 2025-11-28WEIFANG TIANDE PIPE IND CO LTD

Patent Information

Application Number
CN202511566516.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-30
Publication Date
2025-11-28
Estimated Expiration
2045-10-30

AI Technical Summary

Technical Problem

In existing 3PE anti-corrosion technology, epoxy powder coatings have poor leveling properties during the application process, which leads to voids between the anti-corrosion layer and the anchor pattern on the steel pipe surface, reducing the resistance to cathodic disbondment and affecting the bonding strength of the anti-corrosion layer.

Method used

Low molecular weight bisphenol A epoxy resin and 2-methylimidazolium-propylmaleic anhydride are used as curing agents, combined with silanized nanoparticle suspension to treat the surface of steel pipes, and then electrostatic spraying is used to form inner and outer anti-corrosion layers, improving leveling effect and adhesion.

Benefits of technology

It enhances the leveling effect and adhesion of epoxy powder coating on the steel pipe surface, improves the anti-cathode disbondment resistance and overall strength of the anti-corrosion layer, and ensures a tight bond between the anti-corrosion layer and the steel pipe surface.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of anti-corrosion pipelines, and particularly relates to an outer 3PE inner epoxy resin anti-corrosion pipeline and a production process thereof. Medium-frequency preheating; performing internal and external shot blasting to remove rust; carrying out silanization nanoparticle suspension liquid treatment; internal corrosion prevention; epoxy powder coating is sprayed on the outer surface of the steel pipe through an electrostatic spraying technology to form an anti-corrosion bottom layer, and the outer surface of the steel pipe is coated with adhesive and polyethylene to form an adhesive layer and a polyethylene layer. According to the invention, bisphenol A epoxy resin with low molecular weight is selected, and the molten epoxy powder coating has relatively low viscosity and can be fully infiltrated into the bottom of an anchor pattern on the surface of the steel pipe, so that the leveling effect is improved, the leveling time is shortened, and the epoxy resin coating is more uniform; meanwhile, under the promotion of an imidazole group, acid anhydride and bisphenol A epoxy resin are quickly crosslinked and cured to form gel, so that the viscosity of the epoxy powder coating is quickly increased, and sagging is prevented.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of anticorrosion pipelines, and particularly relates to an outer 3PE inner epoxy resin anticorrosion pipeline and a production process thereof. BACKGROUND

[0002] In recent years, with the development of oil and gas resources, the 3PE anticorrosion technology has been widely applied in buried pipelines, but phenomena such as anticorrosion layer peeling failure and pipeline perforation have occurred during service, which even causes oil and gas leakage, explosion, and great economic loss and safety accidents.

[0003] The main method of the 3PE anticorrosion technology of the pipeline is: firstly, the steel pipe is preheated and then the surface is pretreated; then the steel pipe is heated to a suitable coating temperature, and the epoxy powder coating is uniformly coated on the surface of the steel pipe; the adhesive is coated and the polyethylene is coated in the process of curing of the epoxy powder coating. The core of the 3PE anticorrosion technology is the crosslinking and curing of the epoxy powder coating, and the epoxy powder coating is sprayed on the surface of the steel pipe by a high-voltage electrostatic spray gun, and finally solidified into a film through coalescence, leveling and melting crosslinking.

[0004] The cathodic peeling resistance is an important index for evaluating the 3PE anticorrosion layer, and has become a key index for measuring the advantages and disadvantages of the anticorrosion layer. In the coating process of the existing epoxy powder coating, the leveling performance of the epoxy powder is poor, and in the melting process, the epoxy powder does not flow fully to the anchor bottom of the steel pipe surface, and a hollow is formed between the anchor bottom and the anticorrosion layer, which directly causes the false bonding between the anticorrosion layer and the anchor of the steel pipe surface, and reduces the cathodic peeling resistance of the anticorrosion layer. SUMMARY

[0005] The purpose of the application is to provide an outer 3PE inner epoxy resin anticorrosion pipeline and a production process thereof, so as to solve the above technical problems.

[0006] In order to achieve the above technical purpose, the technical scheme of the application is: An outer 3PE inner epoxy resin anticorrosion pipeline production process, comprising the following steps: S1, online inspection; Detecting that the surface of the steel pipe is free of mechanical damage, pits, peeling, scarring and oil pollution phenomena; S2, medium frequency preheating; The temperature of the steel pipe is preheated to 40-60 DEG C; S3, inner and outer shot blasting derusting; The shot blasting abrasive is projected to the inner and outer surfaces of the steel pipe by high-speed rotation of the shot head, so that the derusting grade of the surface of the steel pipe reaches Sa2.5, and the surface roughness is 65-75 mu m, and then the inner and outer surfaces of the steel pipe are blown by clean and dry compressed air; S4, silanization nano-particle suspension treatment; Spray the silanized nano-ion suspension to the inner and outer surface of the steel pipe, and then dry at 105-110℃ for 2-2.5h; S5, inner anticorrosion; Heat the steel pipe to 200-210℃, spray the epoxy powder coating on the inner surface of the steel pipe by electrostatic spraying technology, and form the inner anticorrosion layer after cooling, with a coating line speed of 1.8-2m / min; S6, outer anticorrosion; Heat the steel pipe to 200-210℃, spray the epoxy powder coating on the outer surface of the steel pipe by electrostatic spraying technology to form the anticorrosion primer layer, with a coating line speed of 1.8-2m / min, and then perform adhesive and polyethylene coating molding on the outer surface of the steel pipe to form the adhesive layer and the polyethylene layer, and cool the coated steel pipe to below 60℃ by water cooling to obtain the outer 3PE inner epoxy resin anticorrosion pipe.

[0007] As a further improvement, the preparation method of the epoxy powder coating comprises the following steps: S11, add propyl maleopimaric anhydride, pyridine, dichlorosulfoxide and N,N-dimethylformamide into solvent 1,2-dichloroethane, reflux at 60-65℃ for 1-1.2h, and then add an equal volume of n-hexane to the reaction liquid, distill at 60℃, and dry the remaining product to obtain propyl maleopimaric anhydride acyl chloride; S12, add propyl maleopimaric anhydride acyl chloride into tetrahydrofuran, and fully stir and dissolve under ice bath to obtain reaction liquid A; Add 2-methylimidazole into tetrahydrofuran, fully stir and dissolve, then add triethylamine and mix uniformly to obtain reaction liquid B; Add reaction liquid B dropwise into reaction liquid A, seal, and stir at 40-45℃ for 4-4.5h, filter after the reaction is completed, collect the solid by rotary evaporation, wash with water, and dry to obtain 2-methylimidazole-propyl maleopimaric anhydride; S13, mix bisphenol A type epoxy resin, 2-methylimidazole-propyl maleopimaric anhydride, filler, leveling agent, pigment, and benzoin, and then send into an extruder, the screw diameter of the extruder is 53mm, the length-diameter ratio is 16:1, melt extrude to obtain the material, crush after cooling, pass through an 80 mesh sieve, and obtain the epoxy powder coating, the epoxy value of the bisphenol A type epoxy resin is 0.2-0.25eq / 100g.

[0008] As a further improvement, in step S11, the preparation method of propyl maleopimaric anhydride is as follows: mix gasoline and rosin, heat to dissolve and clarify, slowly add cyclohexylamine oil solution into the mixture, and keep at 40℃ for 1h, then cool to 0-5℃ in an ice water bath for 30min, wash the obtained filter cake with 0-5℃ gasoline for 3 times, and dry to obtain solid. The solid is ground into powder and mixed with ethyl ether to obtain a suspension, hydrochloric acid solution is added to the suspension, stirring until the powder is dissolved, continue stirring for 30 min, then stand still, remove the water phase, wash the organic phase with distilled water until the pH of the water phase is 6, remove the ethyl ether in the organic phase by atmospheric distillation, and vacuum drying to obtain resin acid; The resin acid, 3-propyl furan-2, 5-dione, p-toluene sulfonic acid and glacial acetic acid are mixed, heated to melt the materials under nitrogen atmosphere, then the temperature is raised to 180~185℃ and stirred for 4~5h, after the reaction is completed, the temperature is lowered to 110℃, then 100mL of glacial acetic acid is added to the reaction system, stirred uniformly, cooled to room temperature, then cooled to 0~5℃ and filtered to obtain white solid, which is recrystallized with glacial acetic acid and vacuum dried to obtain propyl male pimaric anhydride.

[0009] As a further improvement, the molar ratio of resin acid, 3-propyl furan-2, 5-dione and p-toluene sulfonic acid is 1.8~2:1:0.1, and the mass-volume ratio of 3-propyl furan-2, 5-dione to glacial acetic acid is 1g:2~2.5mL.

[0010] As a further improvement, in step S11, the molar ratio of propyl male pimaric anhydride, pyridine, dichlorosulfoxide and N,N-dimethylformamide is 1:1:3:0.01; In step S12, in reaction liquid A, 1mmol of propyl male pimaric anhydride chloride is added per 1mL of tetrahydrofuran; in reaction liquid B, 1mmol of 2-methylimidazole is added per 1mL of tetrahydrofuran, and the molar ratio of 2-methylimidazole to triethylamine is 1:1; the volume ratio of reaction liquid A to reaction liquid B is 1:1; In step S13, the temperature of the extruder is: zone 1 50~55℃, zone 2 90~95℃, and zone 3 70~75℃.

[0011] As a further improvement, in step S13, the components of the epoxy powder coating are as follows in terms of weight percentage: bisphenol A type epoxy resin 55~65%, 2-methylimidazole-propyl male pimaric anhydride 1~5%, filler 30~38%, leveling agent 1~1.5%, pigment 1~2%, and benzoin 0.5~1%.

[0012] As a further improvement, the preparation method of the silanized nanoparticle suspension is as follows: in a mixture of ethanol and water with a mass ratio of 9:1, dodecyltrimethoxysilane is added, stirred at 2000r / min at room temperature for 20~30min, then nano-aluminum oxide particles are added and continue to stir for 10~15min to obtain a suspension, and the suspension is ultrasonically dispersed for 20min to obtain a silanized nanoparticle suspension.

[0013] As a further improvement, the mass ratio of the nano-aluminum oxide particles and the dodecyl trimethoxysilane is 1:1.2, and the mass ratio of the dodecyl trimethoxysilane and the ethanol-water mixture is 1:50.

[0014] The application further provides an outer 3PE and inner epoxy resin anticorrosion pipeline.

[0015] Due to the adoption of the above technical solutions, the application has the following beneficial effects: The outer 3PE and inner epoxy resin anticorrosion pipeline and the production process thereof provided by the application select a low-molecular-weight bisphenol A epoxy resin, the viscosity of the melted epoxy powder coating is relatively low, the epoxy powder coating can fully infiltrate into the anchor bottom of the steel pipe surface, the flow leveling effect is improved, the flow leveling time is shortened, and the epoxy resin coating is more uniform; meanwhile, 2-methyl imidazole-propyl male pimaric anhydride is used as a curing agent, under the promotion of the imidazole group, the anhydride is quickly crosslinked and solidified with the bisphenol A epoxy resin to form a gel, so that the viscosity of the epoxy powder coating is rapidly increased to prevent sagging.

[0016] In the application, under the promotion of the imidazole group, the epoxy powder coating forms more hydroxyl groups in a shorter time, and the adhesion to the steel pipe substrate is improved.

[0017] In the application, the hydrogen phenanthrene ring rigid structure in the 2-methyl imidazole-propyl male pimaric anhydride curing agent can improve the surface tension of the epoxy resin before the epoxy resin is gelled, prevent the surface tension from decreasing too fast and too much during the curing process, and prevent the initial good wetting state from being destroyed and even retracted, thereby affecting the adhesion between the epoxy resin and the steel pipe.

[0018] In the application, after the epoxy powder coating is cured, the octyl long chain in the 2-methyl imidazole-propyl male pimaric anhydride curing agent extends to the side away from the outer wall of the steel pipe, improves the compatibility with the polypropylene adhesive, improves the strength of the anticorrosion layer, and at the same time, the surface of the steel pipe is treated by using the silanized nano ionic suspension, so that a silanized film is formed on the surface of the steel pipe, the dodecyl long chain in the silanized film and the octyl long chain in the epoxy powder coating are staggered and inserted, and the adhesion between the epoxy powder coating and the outer wall of the steel pipe is further improved. DETAILED DESCRIPTION

[0019] The technical solutions of the present application will be clearly and completely described below in conjunction with specific embodiments, but those skilled in the art will understand that the following described embodiments are part of the embodiments of the present application, not all the embodiments, and are only used to illustrate the present application, and should not be regarded as limiting the scope of the present application. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative labor fall within the scope of protection of the present application. If the specific conditions are not specified in the embodiments, the conventional conditions or the conditions recommended by the manufacturer are used. If the reagents or instruments used are not specified by the manufacturer, they are all conventional products that can be purchased on the market.

[0020] In the present application, the leveling agent and the pigment are specific components of the leveling agent and the pigment that can be used in the existing technology of the epoxy powder coating, for example: the leveling agent can be selected from acrylate polymers or polysiloxanes, etc., and the pigment can be selected from titanium dioxide or carbon black, etc., which are not specifically limited in the present application, and the specific components of the leveling agent and the filler will not affect the various performances of the anti-corrosion pipeline.

[0021] Example 1: A production process of an outer 3PE inner epoxy resin anti-corrosion pipeline, comprising the following steps: S1, online inspection; detecting that the surface of the steel pipe is free of mechanical damage, pits, peeling, scarring and oil contamination; S2, medium frequency preheating; preheating the temperature of the steel pipe to 40℃; S3, inner and outer shot blasting; using shot blasting abrasive to be projected to the inner and outer surfaces of the steel pipe by high-speed rotation of the throwing head, so that the rust removal grade of the surface of the steel pipe reaches Sa2.5 level, and the surface roughness is 65μm, and then the inner and outer surfaces of the steel pipe are blown with clean and dry compressed air; S4, silanized nanoparticle suspension treatment; spraying the silanized nanoparticle suspension to the inner and outer surfaces of the steel pipe, and then drying at 105℃ for 2.5h; S5, inner anti-corrosion; heating the steel pipe to 200℃, and spraying the epoxy powder coating on the inner surface of the steel pipe by using electrostatic spraying technology, and forming an inner anti-corrosion layer after cooling, and the coating line speed is 1.8m / min; S6, outer anti-corrosion; heating the steel pipe to 200℃, and spraying the epoxy powder coating on the outer surface of the steel pipe by using electrostatic spraying technology to form an anti-corrosion primer layer, and the coating line speed is 1.8m / min, and the adhesive layer and the polyethylene layer are formed by adhesive and polyethylene coating molding on the outer surface of the steel pipe, and the coated steel pipe is cooled to below 60℃ by water cooling to obtain an outer 3PE inner epoxy resin anti-corrosion pipeline.

[0022] In the embodiment, the production process of the anti-corrosion steel pipe is different from the production process of the anti-corrosion steel pipe in the prior art in that the silanized nano-particle suspension is treated, the epoxy powder coating used and the coating line speed of the epoxy powder coating, and the other steps are the same as those in the prior art.

[0023] In the embodiment, the steel pipe is a conventional pipe with DN200.

[0024] In the embodiment, the silanized nano-particle suspension is prepared by adding 20 g of dodecyltrimethoxysilane to 1000 g of a mixture of ethanol and water with a mass ratio of 9:1, stirring at room temperature at 2000 r / min for 20 min, then adding 16.67 g of nano-aluminum oxide particles to the mixture, and continuing to stir for 10 min to obtain the suspension, and then ultrasonic dispersing the suspension for 20 min to obtain the silanized nano-particle suspension.

[0025] In the embodiment, the preparation method of the epoxy powder coating comprises the following steps: S11, preparing propyl maleopimaric anhydride; 600 L of gasoline and 200 kg of rosin are mixed, heated to 40℃ to be dissolved and clear, 100 L of 3 kg / 25 L of cyclohexylamine oil solution is slowly added to form a large amount of white precipitate, then incubated at 40℃ for 1 h, after the reaction is completed, cooled to 0℃ in an ice water bath for 30 min, the filter cake obtained after suction filtration is washed with 50 L of 0℃ gasoline for 3 times, and then vacuum dried at 40℃ to obtain a solid; The cyclohexylamine oil solution is obtained by dissolving 3 kg of cyclohexylamine in 25 L of gasoline; The solid is ground into powder and mixed with 150 L of diethyl ether to obtain a suspension, 150 L of 3 mol / L hydrochloric acid solution is added to the suspension, and the powder is stirred to dissolve, then continues to stir for 30 min and stands, the water phase is removed, the organic phase is washed with distilled water until the pH of the water phase is 6, the diethyl ether in the organic phase is removed by atmospheric distillation, and the resin acid is obtained by vacuum drying at 40℃; The resin acid, 3-propyl furan-2,5-dione, p-toluenesulfonic acid and glacial acetic acid are mixed, the molar ratio of the resin acid, 3-propyl furan-2,5-dione and p-toluenesulfonic acid is 1.8:1:0.1, the mass-volume ratio of 3-propyl furan-2,5-dione and glacial acetic acid is 1 kg:2 L, heated to melt the materials under nitrogen atmosphere, then the temperature is increased to 180℃ under stirring for 5 h, after the reaction is completed, the temperature is decreased to 110℃, then 100 L of glacial acetic acid is added to the reaction system and stirred uniformly, cooled to room temperature, then cooled to 0℃ with ice water, and suction filtered to obtain a white solid, the white solid is recrystallized with glacial acetic acid, and then vacuum dried at 60℃ to obtain propyl maleopimaric anhydride; The reaction equation is as follows: ; S12, preparing propyl maleopimaric anhydride acyl chloride; Propyl maleopimaric anhydride, pyridine, dichloro sulfoxide and N, N-dimethylformamide (DMF) were added into solvent 1, 2-dichloroethane in a molar ratio of 1:1:3:0.01, and refluxed at 60℃ for 1h. After the reaction was completed, the reaction liquid was obtained. An equal volume of n-hexane was added to the reaction liquid, and distilled at 60℃. The remaining product was vacuum dried at 40℃ for 1h to obtain propyl maleopimaric anhydride acyl chloride. The reaction equation is as follows: ; S13, preparing 2-methyl imidazole-propyl maleopimaric anhydride; Propyl maleopimaric anhydride acyl chloride was added into tetrahydrofuran, and fully stirred and dissolved in an ice bath to obtain reaction liquid A (tetrahydrofuran solution of propyl maleopimaric anhydride acyl chloride). In reaction liquid A, 1 mol of propyl maleopimaric anhydride acyl chloride was added per 1L of tetrahydrofuran. 2-methyl imidazole was added into tetrahydrofuran, fully stirred and dissolved, and then triethylamine was added thereto and uniformly mixed to obtain reaction liquid B. Reaction liquid B was added dropwise into reaction liquid A, sealed, and stirred at 40℃ for 4h. After the reaction was completed, the filtrate was collected by rotary evaporation, washed with water, and dried at 50℃ for 12h to obtain 2-methyl imidazole-propyl maleopimaric anhydride. In reaction liquid B, 1 mol of 2-methyl imidazole was added per 1L of tetrahydrofuran, and the molar ratio of 2-methyl imidazole to triethylamine was 1:1. The volume ratio of reaction liquid A to reaction liquid B was 1:1. The reaction equation is as follows: ; S14, in weight percentage, bisphenol A epoxy resin 60%, 2-methyl imidazole-propyl maleopimaric anhydride 1.5%, filler calcium carbonate 35%, leveling agent 1.2%, pigment 1.5%, benzoin 0.8% were respectively weighed and mixed, and then fed into an extruder. The screw diameter of the extruder was 53mm, and the length-diameter ratio was 16:1. The material was melt-extruded to obtain an epoxy powder coating. The temperature of the extruder was: zone 1 50℃, zone 2 90℃, and zone 3 70℃. The epoxy value of the bisphenol A epoxy resin was 0.2 eq / 100g.

[0026] Example 2, a production process of an outer 3PE and inner epoxy resin anticorrosion pipeline, including the following steps: S1, online inspection; detecting that the surface of the steel pipe is free of mechanical damage, pits, peeling, scarring and oil contamination; S2, medium frequency preheating; preheating the temperature of the steel pipe to 60℃; S3, inner and outer shot blasting; the shot blasting abrasive is thrown to the inner and outer surface of the steel pipe by the high-speed rotation of the throwing head, so that the steel pipe surface reaches the Sa2.5 grade of rust removal level and the surface roughness is 75 μm, and then the inner and outer surface of the steel pipe is blown by clean and dry compressed air; S4, silanized nanoparticle suspension treatment; the silanized nanoparticle suspension is sprayed to the inner and outer surface of the steel pipe, and then dried at 110℃ for 2h; S5, inner corrosion protection; the steel pipe is heated to 210℃, and the epoxy powder coating is sprayed on the inner surface of the steel pipe by electrostatic spraying technology to form an inner corrosion protection layer, and the coating line speed is 2m / min; S6, outer corrosion protection; the steel pipe is heated to 210℃, and the epoxy powder coating is sprayed on the outer surface of the steel pipe by electrostatic spraying technology to form a corrosion protection primer, and the coating line speed is 2m / min, and the adhesive layer and the polyethylene layer are formed by adhesive and polyethylene coating molding on the outer surface of the steel pipe, and the coated steel pipe is cooled to below 60℃ by water cooling to obtain an outer 3PE inner epoxy resin corrosion protection pipe.

[0027] In this embodiment, the silanized nanoparticle suspension treatment, the epoxy powder coating used and the coating line speed of the epoxy powder coating in the production process of the corrosion protection steel pipe are different from the production process of the corrosion protection steel pipe in the prior art, and the other steps are the prior art.

[0028] In this embodiment, the steel pipe is a conventional pipe with DN1000.

[0029] In this embodiment, the preparation method of the silanized nanoparticle suspension is as follows: 20g of dodecyl trimethoxysilane is added to 1000g of ethanol-water mixture with a mass ratio of 9:1, stirred at 2000r / min at room temperature for 30min, then 16.67g of nano-aluminum oxide particles is added, and stirred for another 15min to obtain the suspension, and the suspension is ultrasonically dispersed for 20min to obtain the silanized nanoparticle suspension.

[0030] In this embodiment, the preparation method of the epoxy powder coating includes the following steps: S11, preparation of propyl maleic firtunonic acid anhydride; 600L of gasoline and 200kg of rosin are mixed and heated to 40℃ to dissolve and clarify, 100L of 3kg / 25L cyclohexylamine oil solution is slowly added, a large amount of white precipitate is formed, then the reaction is kept at 40℃ for 1h, after the reaction is completed, the temperature is lowered to 5℃ in an ice water bath for 30min, the filter cake obtained after filtration is washed with 50L of 5℃ gasoline for 3 times, and then vacuum dried at 40℃ to obtain a solid; The cyclohexylamine oil solution is obtained by dissolving 3kg of cyclohexylamine in 25L of gasoline; The solid was ground into powder and mixed with 150 L of ethyl ether to obtain a suspension, 150 L of 3 mol / L hydrochloric acid solution was added to the suspension, and the powder was stirred until dissolved, and then stirred for 30 min, and then allowed to stand, the water phase was removed, the organic phase was washed with distilled water until the pH of the water phase was 6, the ethyl ether in the organic phase was removed by normal pressure distillation, and the resin acid was obtained by vacuum drying at 40°C; The resin acid, 3-propyl furan-2, 5-dione, p-toluenesulfonic acid and glacial acetic acid were mixed, the molar ratio of the resin acid, 3-propyl furan-2, 5-dione and p-toluenesulfonic acid was 2:1:0.1, the mass-volume ratio of 3-propyl furan-2, 5-dione and glacial acetic acid was 1 kg:2.5 L, and the material was heated to melt under a nitrogen atmosphere, then stirred and heated to 185°C for 4 h, after the reaction was completed, the temperature was lowered to 110°C, then 100 L of glacial acetic acid was added to the reaction system and stirred uniformly, and then cooled to room temperature, and then cooled to 5°C with ice water and filtered to obtain a white solid, which was recrystallized with glacial acetic acid and vacuum dried at 60°C to obtain propyl maleopimaric anhydride; S12, preparation of propyl maleopimaric anhydride acyl chloride; The propyl maleopimaric anhydride, pyridine, dichloro sulfoxide and N,N-dimethyl formamide (DMF) were added to solvent 1, 2-dichloroethane according to a molar ratio of 1:1:3:0.01, and refluxed at 65°C for 1.2 h, and then the reaction liquid was obtained, and then an equal volume of n-hexane was added to the reaction liquid, and then distilled at 60°C, and then the remaining product was vacuum dried at 40°C for 1 h to obtain propyl maleopimaric anhydride acyl chloride; S13, preparation of 2-methyl imidazole-propyl maleopimaric anhydride; The propyl maleopimaric anhydride acyl chloride was added to tetrahydrofuran, and then dissolved by stirring in an ice bath to obtain reaction liquid A (propyl maleopimaric anhydride acyl chloride tetrahydrofuran solution); 1 mol of propyl maleopimaric anhydride acyl chloride was added to 1 L of tetrahydrofuran in the reaction liquid A; The 2-methyl imidazole was added to tetrahydrofuran, and then dissolved by stirring, and then 2-methyl imidazole and triethylamine were added thereto and mixed uniformly to obtain reaction liquid B, and then the reaction liquid B was added dropwise to the reaction liquid A, and then sealed and stirred at 45°C for 4.5 h, and then filtered after the reaction was completed, and then the filtrate was collected by rotary evaporation, and then washed with water and dried at 50°C for 12 h to obtain 2-methyl imidazole-propyl maleopimaric anhydride; 1 mol of 2-methyl imidazole was added to 1 L of tetrahydrofuran in the reaction liquid B, and the molar ratio of 2-methyl imidazole and triethylamine was 1:1, and the volume ratio of the reaction liquid A and the reaction liquid B was 1:1; S14, by weight percentage, respectively, take 55% of bisphenol A epoxy resin, 2.5% of 2-methyl imidazole-propyl maleic anhydride, 38% of filler calcium carbonate, 1.5% of leveling agent, 2% of pigment, 1% of benzoin, fully mixed and sent into the extruder, the screw diameter of the extruder is 53mm, the length-diameter ratio is 16:1, melt extrusion to obtain the material cooling, crushing, and sieving through 80 mesh screen to obtain the epoxy powder coating, the temperature of the extruder is: 55℃ in the first zone, 95℃ in the second zone, 75℃ in the third zone; The epoxy value of the bisphenol A epoxy resin is 0.25 eq / 100g.

[0031] The production process of the outer 3PE inner epoxy resin anticorrosion pipeline in this embodiment includes the following steps: S1, online inspection; detecting that the surface of the steel pipe is free of mechanical damage, pits, peeling, scarring and oil contamination; S2, medium frequency preheating; preheating the temperature of the steel pipe to 50℃; S3, inner and outer shot blasting; using shot blasting abrasive to be projected to the inner and outer surfaces of the steel pipe by high-speed rotation of the shot head, so that the rust removal grade of the surface of the steel pipe reaches Sa2.5 level, and the surface roughness is 70μm, and then the inner and outer surfaces of the steel pipe are blown by clean and dry compressed air; S4, silanized nanoparticle suspension treatment; spraying the silanized nanoparticle suspension to the inner and outer surfaces of the steel pipe, and then drying at 108℃ for 2.3h; S5, inner anticorrosion; heating the steel pipe to 205℃, and spraying the epoxy powder coating on the inner surface of the steel pipe by using electrostatic spraying technology to form an inner anticorrosion layer after cooling, and the coating line speed is 1.9m / min; S6, outer anticorrosion; heating the steel pipe to 205℃, and spraying the epoxy powder coating on the outer surface of the steel pipe by using electrostatic spraying technology to form an anticorrosion primer layer, and the coating line speed is 1.9m / min, and then performing adhesive and polyethylene coating molding on the outer surface of the steel pipe to form an adhesive layer and a polyethylene layer, and the coated steel pipe is cooled to below 60℃ by water cooling to obtain the outer 3PE inner epoxy resin anticorrosion pipeline.

[0032] In this embodiment, the silanized nanoparticle suspension treatment, the used epoxy powder coating and the coating line speed of the epoxy powder coating in the production process of the anticorrosion steel pipe are different from the production process of the anticorrosion steel pipe in the prior art, and the other steps are the prior art.

[0033] In this embodiment, the steel pipe is a conventional pipeline with DN500.

[0034] In this embodiment, the preparation method of the silanized nanoparticle suspension is as follows: 20 g of dodecyltrimethoxysilane is added into 1000 g of ethanol-water mixture with a mass ratio of 9:1, stirred at 2000 r / min for 25 min at room temperature, then 16.67 g of nano-aluminum oxide particles is added into the mixture, and the stirring is continued for 13 min to obtain a suspension, and the suspension is ultrasonically dispersed for 20 min to obtain the silanized nanoparticle suspension.

[0035] In this embodiment, the preparation method of the epoxy powder coating includes the following steps: S11, preparing propyl maleopimaric anhydride; 600 L of gasoline and 200 kg of rosin are mixed, heated to 40℃ to dissolve and clarify, 100 L of 3 kg / 25 L cyclohexylamine oil solution is slowly added, a large amount of white precipitate is formed, then the reaction is kept at 40℃ for 1 h, after the reaction is completed, the temperature is reduced to 3℃ in an ice water bath for 30 min, the filter cake obtained after suction filtration is washed with 50 L of 3℃ gasoline for 3 times, and then vacuum dried at 40℃ to obtain a solid; The cyclohexylamine oil solution is obtained by dissolving 3 kg of cyclohexylamine in 25 L of gasoline; The solid is ground into powder and mixed with 150 L of diethyl ether to obtain a suspension, 150 L of 3 mol / L hydrochloric acid solution is added into the suspension, the powder is stirred to dissolve, the stirring is continued for 30 min, then the suspension is left to stand, the water phase is removed, the organic phase is washed with distilled water until the pH of the water phase is 6, the diethyl ether in the organic phase is removed by atmospheric distillation, and the resin acid is obtained by vacuum drying at 40℃; The resin acid, 3-propyl furan-2,5-dione, p-toluenesulfonic acid and glacial acetic acid are mixed, the molar ratio of the resin acid, 3-propyl furan-2,5-dione and p-toluenesulfonic acid is 1.9:1:0.1, the mass-volume ratio of 3-propyl furan-2,5-dione and glacial acetic acid is 1 kg:2.3 L, the material is heated to melt under nitrogen atmosphere, then the temperature is increased to 183℃ for reaction for 4.5 h, after the reaction is completed, the temperature is reduced to 110℃, then 100 L of glacial acetic acid is added into the reaction system, stirred uniformly, cooled to room temperature, then cooled to 3℃ with ice water, and suction filtered to obtain a white solid, the white solid is recrystallized with glacial acetic acid, and then vacuum dried at 60℃ to obtain propyl maleopimaric anhydride; S12, preparing propyl maleopimaric anhydride chloride; The propyl maleopimaric anhydride, pyridine, dichloro sulfoxide and N,N-dimethyl formamide (DMF) are added into solvent 1,2-dichloroethane according to a molar ratio of 1:1:3:0.01, and the reaction is carried out at 63℃ for 1.1 h, after the reaction is completed, a reaction liquid is obtained, an equal volume of n-hexane is added into the reaction liquid, and the mixture is distilled at 60℃, and the remaining product is vacuum dried at 40℃ for 1 h to obtain propyl maleopimaric anhydride chloride; S13, preparing 2-methyl imidazole-propyl maleopimaric anhydride; The propyl maleopimaric anhydride chloride was added into tetrahydrofuran, and dissolved under stirring in an ice bath to obtain reaction liquid A (tetrahydrofuran solution of propyl maleopimaric anhydride chloride); 1 mol of propyl maleopimaric anhydride chloride was added into 1 L of tetrahydrofuran in reaction liquid A; The 2-methyl imidazole was added into tetrahydrofuran, and dissolved under stirring, and then 2-methyl imidazole and triethylamine were mixed uniformly to obtain reaction liquid B, and the reaction liquid B was added dropwise into reaction liquid A, and then sealed and stirred at 43℃ for 4.3 h, and then filtered after the reaction was completed, and the solid was collected by rotary evaporation, and then washed with water and dried at 50℃ for 12 h to obtain 2-methyl imidazole-propyl maleopimaric anhydride; 1 mol of 2-methyl imidazole was added into 1 L of tetrahydrofuran in reaction liquid B, and the molar ratio of 2-methyl imidazole to triethylamine was 1:1, and the volume ratio of reaction liquid A to reaction liquid B was 1:1; S14, by weight percentage, respectively, 65% of bisphenol A epoxy resin, 1% of 2-methyl imidazole-propyl maleopimaric anhydride, 30% of filler calcium carbonate, 1% of leveling agent, 2% of pigment and 1% of benzoin were mixed and then fed into an extruder, the screw diameter of the extruder was 53 mm, the length-diameter ratio was 16:1, and the material was melt-extruded to obtain a powder coating after cooling and crushing through an 80-mesh screen, and the temperature of the extruder was: 53℃ for the first zone, 93℃ for the second zone and 73℃ for the third zone; The epoxy value of the bisphenol A epoxy resin was 0.23 eq / 100 g.

[0036] Example 4 A production process of an outer 3PE and inner epoxy resin anticorrosion pipeline, including the following steps: S1, online inspection; detecting that the surface of the steel pipe is free of mechanical damage, pits, peeling, scarring and oil contamination; S2, medium frequency preheating; preheating the temperature of the steel pipe to 45℃; S3, inner and outer shot blasting; the shot blasting abrasive is projected to the inner and outer surfaces of the steel pipe by high-speed rotation of the throwing head, so that the steel pipe surface reaches Sa2.5 grade in rust removal level and the surface roughness is 68 μm, and then the inner and outer surfaces of the steel pipe are blown with clean and dry compressed air; S4, silanized nanoparticle suspension treatment; the silanized nanoparticle suspension is sprayed to the inner and outer surfaces of the steel pipe, and then dried at 106℃ for 2.2 h; S5, inner anticorrosion; the steel pipe is heated to 200℃, and the epoxy powder coating is sprayed on the inner surface of the steel pipe by electrostatic spraying technology, and then cooled to form an inner anticorrosion layer, and the coating line speed is 1.8 m / min; S6, external corrosion protection; the steel pipe is heated to 210℃, an electrostatic spraying technology is used to spray an epoxy powder coating on the outer surface of the steel pipe to form a corrosion protection primer, the coating line speed is 2m / min, an adhesive and polyethylene are coated on the outer surface of the steel pipe to form an adhesive layer and a polyethylene layer, and the coated steel pipe is cooled to below 60℃ by water cooling to obtain an outer 3PE inner epoxy resin corrosion protection pipe.

[0037] In the embodiment, the silanized nanoparticle suspension treatment, the used epoxy powder coating and the coating line speed of the epoxy powder coating in the production process of the corrosion protection steel pipe are different from the production process of the corrosion protection steel pipe in the prior art, and the other steps are the prior art.

[0038] In the embodiment, the steel pipe is a conventional pipe with DN800.

[0039] In the embodiment, the preparation method of the silanized nanoparticle suspension is as follows: 20g of dodecyltrimethoxysilane is added to 1000g of an ethanol-water mixture with a mass ratio of 9:1, stirred at 2000r / min at room temperature for 28min, then 16.67g of nano-aluminum oxide particles is added thereto, and the stirring is continued for 14min to obtain a suspension, and the suspension is ultrasonically dispersed for 20min to obtain the silanized nanoparticle suspension.

[0040] In the embodiment, the preparation method of the epoxy powder coating includes the following steps: S11, preparing propyl maleic fustic anhydride; 600L of gasoline and 200kg of rosin are mixed, heated to 40℃ to dissolve and clarify, 100L of a 3kg / 25L cyclohexylamine oil solution is slowly added thereto to form a large amount of white precipitate, then the reaction is kept at 40℃ for 1h, after the reaction is completed, the temperature is reduced to 2℃ in an ice water bath for 30min, the filter cake obtained after suction filtration is washed with 50L of 2℃ gasoline for 3 times, and then vacuum dried at 40℃ to obtain a solid; The cyclohexylamine oil solution is obtained by dissolving 3kg of cyclohexylamine in 25L of gasoline; The solid is ground into powder and mixed with 150L of diethyl ether to obtain a suspension, 150L of a 3mol / L hydrochloric acid solution is added to the suspension, the powder is stirred to dissolve, the stirring is continued for 30min, then the suspension is left to stand, the water phase is removed, the organic phase is washed with distilled water until the pH of the water phase is 6, the diethyl ether in the organic phase is removed by atmospheric distillation, and vacuum drying is performed at 40℃ to obtain a resin acid; The resin acid, 3-propyl furan-2, 5-dione, p-toluene sulfonic acid and glacial acetic acid are mixed, the molar ratio of resin acid, 3-propyl furan-2, 5-dione and p-toluene sulfonic acid is 1.8:1:0.1, the mass-volume ratio of 3-propyl furan-2, 5-dione and glacial acetic acid is 1 kg:2 L, heated to melt the material under nitrogen atmosphere, then stirred to 182℃ for 4.2h, after the reaction is completed, the temperature is lowered to 110℃, then 100 L of glacial acetic acid is added to the reaction system, stirred uniformly, cooled to room temperature, then cooled to 2℃ with ice water, filtered, the white solid is recrystallized with glacial acetic acid, then dried at 60℃ under vacuum to obtain propyl maleopimaric anhydride; S12, preparation of propyl maleopimaric anhydride acyl chloride; Propyl maleopimaric anhydride, pyridine, dichloro sulfoxide and N, N-dimethyl formamide (DMF) are added to solvent 1, 2-dichloroethane according to the molar ratio of 1:1:3:0.01, refluxed at 62℃ for 1.05h, after the reaction is completed, the reaction liquid is obtained, the same volume of n-hexane as the reaction liquid is added, distilled at 60℃, the remaining product is dried under vacuum at 40℃ for 1h to obtain propyl maleopimaric anhydride acyl chloride; S13, preparation of 2-methyl imidazole-propyl maleopimaric anhydride; Propyl maleopimaric anhydride acyl chloride is added to tetrahydrofuran, stirred to dissolve under ice bath to obtain reaction liquid A (tetrahydrofuran solution of propyl maleopimaric anhydride acyl chloride); 1 mol of propyl maleopimaric anhydride acyl chloride is added to 1 L of tetrahydrofuran in reaction liquid A; 2-methyl imidazole is added to tetrahydrofuran, stirred to dissolve, then triethylamine is added and mixed uniformly to obtain reaction liquid B, reaction liquid B is added dropwise to reaction liquid A, sealed and stirred at 42℃ for 4.2h, after the reaction is completed, filtered, the filtrate is collected by rotary evaporation, washed with water and dried at 50℃ for 12h to obtain 2-methyl imidazole-propyl maleopimaric anhydride; 1 mol of 2-methyl imidazole is added to 1 L of tetrahydrofuran in reaction liquid B, the molar ratio of 2-methyl imidazole and triethylamine is 1:1, the volume ratio of reaction liquid A and reaction liquid B is 1:1; S14, according to the weight percentage, bisphenol A epoxy resin 55%, 2-methyl imidazole-propyl maleopimaric anhydride 5%, filler calcium carbonate 37%, leveling agent 1.5%, pigment 1%, benzoin 0.5% are weighed respectively, mixed uniformly and sent into the extruder, the screw diameter of the extruder is 53mm, the length-diameter ratio is 16:1, melt extruded to obtain the material, which is cooled, crushed, passed through 80 mesh sieve to obtain the epoxy powder coating, the temperature of the extruder is: zone 1 52℃, zone 2 92℃, zone 3 72℃; The epoxy value of bisphenol A epoxy resin is 0.3 eq / 100g.

[0041] Comparative Example 1 This comparative example provides a production process of a 3PE outer and epoxy resin inner anticorrosive pipeline, and the specific steps are the same as those of Example 1, except that in this comparative example, after the inner and outer surface of the steel pipe is finished by the shot blasting and rust removal, the treatment of the silanization nano-particle suspension is not performed.

[0042] Comparative Example 2 This comparative example provides a production process of a 3PE outer and epoxy resin inner anticorrosive pipeline, and the specific steps are the same as those of Example 1, except that the preparation method of the epoxy powder coating is different from that of Example 1, and the preparation method of the epoxy powder coating is as follows: The bisphenol A epoxy resin 60%, dicyandiamide 1.1%, 2-methyl imidazole 0.4%, filler calcium carbonate 35%, leveling agent 1.2%, pigment 1.5%, benzoin 0.8% are weighed by weight percentage respectively, and then mixed fully and sent into an extruder, the screw diameter of the extruder is 53 mm, the length-diameter ratio is 16:1, and the material is cooled and crushed after melt extrusion, and then sieved through an 80-mesh sieve to obtain the epoxy powder coating, the temperature of the extruder is: 50°C in the first zone, 90°C in the second zone, and 70°C in the third zone. The epoxy value of the bisphenol A epoxy resin is 0.2 eq / 100 g.

[0043] Comparative Example 3 This comparative example provides a production process of a 3PE outer and epoxy resin inner anticorrosive pipeline, and the specific steps are the same as those of Comparative Example 2, except that in this comparative example, the coating line speed of the epoxy powder coating on the inner and outer surfaces of the steel pipe is set to 1.6 m / min.

[0044] Comparative Example 4 This comparative example provides a production process of a 3PE outer and epoxy resin inner anticorrosive pipeline, and the specific steps are the same as those of Comparative Example 2, except that in this comparative example, the coating line speed of the epoxy powder coating on the inner and outer surfaces of the steel pipe is set to 1.4 m / min.

[0045] Comparative Example 5 This comparative example provides a production process of a 3PE outer and epoxy resin inner anticorrosive pipeline, and the specific steps are the same as those of Example 1, except that the preparation method of the epoxy powder coating is different from that of Example 1, and the preparation method of the epoxy powder coating is as follows: S11, preparing maleopimaric anhydride; 600 L of gasoline and 200 kg of rosin are mixed, heated to 40°C to dissolve and clarify, 100 L of 3 kg / 25 L cyclohexylamine oil solution is slowly added, a large amount of white precipitate is formed, then the reaction is kept at 40°C for 1 h, after the reaction is completed, the temperature is reduced to 0°C in an ice water bath for 30 min, the filter cake obtained after suction filtration is washed with 50 L of 0°C gasoline for 3 times, and then vacuum dried at 40°C to obtain a solid; The cyclohexylamine oil solution is obtained by dissolving 3 kg of cyclohexylamine in 25 L of gasoline; The solid was ground into powder and mixed with 150 L of ethyl ether to obtain a suspension, 150 L of 3 mol / L hydrochloric acid solution was added to the suspension, and the powder was stirred until it was dissolved. After 30 min of continuous stirring, the mixture was allowed to stand, the aqueous phase was removed, and the organic phase was washed with distilled water until the pH of the aqueous phase was 6. The ethyl ether in the organic phase was removed by atmospheric distillation, and the resin acid was obtained by vacuum drying at 40°C; The resin acid, maleic anhydride, p-toluenesulfonic acid, and glacial acetic acid were mixed, the molar ratio of the resin acid, maleic anhydride, and p-toluenesulfonic acid was 1.8:1:0.1, the mass-volume ratio of maleic anhydride to glacial acetic acid was 1 kg:2 L, and the mixture was heated to melt under a nitrogen atmosphere. Then, the mixture was stirred and heated to 180°C for 5 h. After the reaction was completed, the mixture was cooled to 110°C, 100 L of glacial acetic acid was added to the reaction system, and the mixture was stirred uniformly. After being cooled to room temperature, the mixture was cooled to 0°C with ice water, and then filtered to obtain a white solid. The white solid was recrystallized with glacial acetic acid and vacuum dried at 60°C to obtain maleopimaric anhydride. S12, maleopimaric anhydride chloride was prepared; Maleopimaric anhydride, pyridine, dichlorosulfoxide, and N,N-dimethylformamide (DMF) were added to solvent 1,2-dichloroethane in a molar ratio of 1:1:3:0.01, and the mixture was refluxed at 60°C for 1 h. After the reaction was completed, a reaction solution was obtained. An equal volume of n-hexane was added to the reaction solution, and the mixture was distilled at 60°C. The remaining product was vacuum dried at 40°C for 1 h to obtain maleopimaric anhydride chloride. S13, 2-methylimidazole-maleopimaric anhydride was prepared; Maleopimaric anhydride chloride was added to tetrahydrofuran, and the mixture was stirred and dissolved in an ice bath to obtain reaction solution A (maleopimaric anhydride chloride tetrahydrofuran solution). In reaction solution A, 1 mol of maleopimaric anhydride chloride was added to 1 L of tetrahydrofuran. 2-Methylimidazole was added to tetrahydrofuran, and the mixture was stirred and dissolved. Then, triethylamine was added to the mixture, and the mixture was stirred uniformly to obtain reaction solution B. Reaction solution B was added dropwise to reaction solution A, and the mixture was sealed and stirred at 40°C for 4 h. After the reaction was completed, the mixture was filtered, and the filtrate was collected by rotary evaporation. After being washed with water, the mixture was dried at 50°C for 12 h to obtain 2-methylimidazole-maleopimaric anhydride. In reaction solution B, 1 mol of 2-methylimidazole was added to 1 L of tetrahydrofuran, and the molar ratio of 2-methylimidazole to triethylamine was 1:1. The volume ratio of reaction solution A to reaction solution B was 1:1. S14, respectively, take bisphenol A epoxy resin 60%, 2-methyl imidazole-maleic anhydride 1.5%, filler calcium carbonate 35%, leveling agent 1.2%, pigment 1.5%, benzoin 0.8% by weight percentage, fully mixed into the extruder, the screw diameter of the extruder is 53mm, the length-diameter ratio is 16:1, melt extrusion to obtain material cooling, crushing, 80 mesh sieve, get epoxy powder coating, the temperature of the extruder is: 50℃ in the first zone, 90℃ in the second zone, 70℃ in the third zone.

[0046] Comparative Example 6 This comparative example provides a production process of outer 3PE inner epoxy resin anticorrosion pipeline, the specific steps are the same as example 1, the difference is that the preparation method of silanized nano particle suspension is different from example 1, the specific steps are as follows: In 1000g mass ratio of 9:1 ethanol-water mixture, add 20g ethyl trimethoxysilane, 2000r / min stirring at room temperature for 20min, then add 16.67g nano alumina particles to it, continue to stir for 10min to get the suspension, ultrasonic dispersion for 20min to get the silanized nano particle suspension.

[0047] Comparative Example 7 This comparative example provides a production process of outer 3PE inner epoxy resin anticorrosion pipeline, the specific steps are the same as example 4, the difference is that, after the inner and outer shot blasting derusting is completed, the silanized nano particle suspension is not treated.

[0048] The anticorrosion pipeline obtained by example 1 and comparative examples 1-7 is tested for cathodic stripping performance, the specific method is as follows: Cut 100mm×100mm sample on the anticorrosion steel pipe obtained by example 1 and comparative examples 1-7, first use 25kV spark leak detector to detect leakage, confirm no leakage point, drill a 6.4mm diameter hole in the center of the sample, drill through the anticorrosion layer, and leak out the metal. Put the plastic cylinder with an outer diameter of 75mm on the sample, seal the contact between the plastic cylinder and the sample with sealant, form a test tank. After the sealant is cured, add 10mL of 3% sodium chloride solution to the plastic cylinder, connect the platinum electrode to the positive electrode of the direct current source, and the metal part of the sample is connected to the negative electrode. The whole device is put into a 65℃ electric incubator, and a direct current of-1.5V is applied.

[0049] After 30 days, the plastic cylinder was removed, the sample was taken out, and cooled to room temperature. A small knife was used to draw a cross shape from the center of the round hole, and the coating was cut outwards along the cross shape until the metal substrate was reached. The cutting distance was at least 20 mm. A sharp knife was inserted from the hole to the bottom of the corrosion protection layer, and the coating was pried in the horizontal direction along the cutting line until the corrosion protection layer showed obvious resistance to prying. The prying distance was measured from the edge of the hole, and was the cathodic disbonding distance of the sample. The cathodic disbonding distance results of the corrosion resistant steel pipes of Example 1 and Comparative Examples 1-7 are shown in Table 1.

[0050] Table 1 Cathodic disbonding distance of the corrosion resistant steel pipes of Example 1 and Comparative Examples 1-7 ; As can be seen from Table 1, the cathodic disbonding resistance of Example 1 is the best. The cathodic disbonding resistance of Comparative Example 1 is lower than that of Comparative Example 6 and Example 1, which is because the steel pipe surface is treated with a silanized nanoparticle suspension to form a silanized film on the surface of the steel pipe, which improves the adhesion between the epoxy powder coating. The silanized nanoparticle suspension is prepared using dodecyltrimethoxysilane, and the long chain dodecyl in the silanized film and the long chain octyl in the epoxy powder coating are interlaced, which further improves the adhesion between the epoxy powder coating and the outer wall of the steel pipe, thereby improving the cathodic disbonding resistance. In Comparative Examples 5 and 6, the long chain interlacing cannot be formed, which reduces the cathodic disbonding resistance.

[0051] Comparative Examples 2-4 and Comparative Example 7 have lower cathodic disbonding resistance than Example 1, and the cathodic disbonding resistance of Comparative Examples 2-4 gradually increases. This is because the molecular weight of the bisphenol A epoxy resin in the epoxy powder coating is low, and the high coating speed in Comparative Example 2 causes the epoxy powder coating to not fully cure, thereby reducing the cathodic disbonding resistance.

[0052] In order to verify the low curing degree of the epoxy powder coating in Comparative Example 2, a differential scanning calorimetry (DSC) test was performed, and the specific test method is as follows: 10 mg of the epoxy powder coating in Comparative Example 2 was placed in a pre-weighed sample pan, covered with a sealing cover, sealed and weighed. The epoxy powder coating was scanned for heat release, and under program temperature control, heated from 25°C to 70°C, and finally cooled to room temperature. The sample was then heated from 25°C to 285°C, then rapidly cooled to 25°C, and then heated from 25°C to 150°C. The Tg2 and ΔH of the epoxy powder were obtained after the end of the test.

[0053] Take 10 mg of the preservative bottom layer in Comparative Example 2 as a preservative layer sample, put it into a pre-weighed sample dish, cover it with a sealing cover, seal and weigh; under the control of the program temperature, heat from 25°C to 110°C, keep at 110°C for 1.5 min, quench the sample to 25°C, then heat the sample from 25°C to 285°C, then quench the sample to 25°C, then heat the sample from 25°C to 150°C, after the end, the Tg4 and ΔH1 of the epoxy powder can be obtained.

[0054] The absolute value of ΔTg |ΔTg| is used as an index to evaluate the curing degree of the epoxy powder.

[0055] The above method is used to measure Example 1, Comparative Example 3 and Comparative Example 4, and the absolute value of ΔTg |ΔTg| of Example 1 and Comparative Examples 2-4 is shown in Table 2.

[0056] Table 2 |ΔTg| results of Example 1 and Comparative Examples 2-4 ; As can be seen from Table 2, the |ΔTg| values of Comparative Examples 2-4 gradually decrease, indicating that the formula of the epoxy powder coating in Comparative Example 2 needs more curing time to completely cure.

[0057] The specific embodiments of the application described above do not constitute a limitation on the scope of protection of the application. Any various other corresponding changes and modifications made according to the technical concept of the application shall be included in the scope of protection of the claims of the application.

Claims

1. A manufacturing process for an external 3PE and internal epoxy resin anti-corrosion pipe, characterized in that, Includes the following steps: S1. Online inspection; The surface of the steel pipe was inspected and found to be free of mechanical damage, dents, peeling, scarring, and oil contamination. S2, Medium-frequency preheating; Preheat the steel pipe to 40~60℃; S3. Internal and external shot blasting for rust removal; Shot blasting abrasive is used to propel the steel pipe onto its inner and outer surfaces at high speed through a rotating shot blasting head, so that the steel pipe surface rust removal grade reaches Sa2.5 and the surface roughness is 65~75μm. Then, clean and dry compressed air is used to blow the inner and outer surfaces of the steel pipe. S4, silanized nanoparticle suspension treatment; The silanized nano-ionic suspension was sprayed onto the inner and outer surfaces of the steel pipe and then dried at 105~110℃ for 2~2.5h. S5, Internal corrosion protection; The steel pipe is heated to 200~210℃, and epoxy powder coating is sprayed on the inner surface of the steel pipe using electrostatic spraying technology. After cooling, an inner anti-corrosion layer is formed. The coating line speed is 1.8~2m / min. S6. External corrosion protection; The steel pipe is heated to 200~210℃, and an epoxy powder coating is sprayed onto the outer surface of the steel pipe using electrostatic spraying technology to form an anti-corrosion base layer. The coating speed is 1.8~2m / min. Adhesive and polyethylene are then coated onto the outer surface of the steel pipe to form an adhesive layer and a polyethylene layer. The coated steel pipe is then cooled to below 60℃ by water cooling to obtain an outer 3PE and inner epoxy resin anti-corrosion pipe.

2. The manufacturing process for the external 3PE and internal epoxy resin anti-corrosion pipe according to claim 1, characterized in that, The preparation method of the epoxy powder coating includes the following steps: S11. Propyl maleic anhydride, pyridine, sulfoxide and N,N-dimethylformamide are added to solvent 1,2-dichloroethane and refluxed at 60~65℃ for 1~1.2h. After the reaction is completed, a reaction solution is obtained. An equal volume of n-hexane is added to the reaction solution and distilled at 60℃. The remaining product is dried to obtain propyl maleic anhydride acyl chloride. S12. Add propyl maleic anhydride chloride to tetrahydrofuran and stir thoroughly in an ice bath to dissolve it, thus obtaining reaction solution A; 2-Methylimidazole was added to tetrahydrofuran and stirred thoroughly to dissolve it. Then, triethylamine was added to the solution and mixed evenly to obtain reaction solution B. Add reaction solution B dropwise to reaction solution A, seal the container, and stir the mixture at 40-45°C for 4-4.5 hours. After the reaction is complete, filter the mixture, collect the solid by rotary evaporation of the filtrate, wash it with water, and dry it to obtain 2-methylimidazolium-propylmaleic anhydride. S13. Weigh out bisphenol A type epoxy resin, 2-methylimidazolium-propylmaleic anhydride, filler, leveling agent, pigment, and benzoin, mix them thoroughly, and feed them into an extruder. The screw diameter of the extruder is 53 mm, and the length-to-diameter ratio is 16:

1. After melt extrusion, the material is cooled, pulverized, and passed through an 80-mesh sieve to obtain an epoxy powder coating. The epoxy value of the bisphenol A type epoxy resin is 0.2~0.25 eq / 100g.

3. The manufacturing process for the external 3PE and internal epoxy resin anti-corrosion pipe according to claim 2, characterized in that, In step S11, the preparation method of propylmaleic anhydride is as follows: gasoline and rosin are mixed and heated to dissolve and clarify. Cyclohexylamine oil solution is slowly added to it and the reaction is kept at 40°C for 1 hour. After the reaction is completed, the temperature is lowered to 0~5°C in an ice-water bath and kept for 30 minutes. The filter cake obtained after filtration is washed three times with gasoline at 0~5°C and then dried to obtain a solid. The solid was ground into powder and mixed with diethyl ether to obtain a suspension. Hydrochloric acid solution was added to the suspension and stirred until the powder dissolved. After stirring for 30 minutes, the mixture was allowed to stand to remove the aqueous phase. The organic phase was washed with distilled water until the pH of the aqueous phase was 6. The diethyl ether in the organic phase was removed by atmospheric distillation and the resin acid was obtained by vacuum drying. Resin acid, 3-propylfuran-2,5-dione, p-toluenesulfonic acid and glacial acetic acid were mixed and heated under a nitrogen atmosphere until the materials melted. Then, the mixture was stirred and heated to 180-185℃ for 4-5 hours. After the reaction was completed, the temperature was lowered to 110℃. Then, 100 mL of glacial acetic acid was added to the reaction system and stirred evenly. After cooling to room temperature, the mixture was cooled to 0-5℃ and filtered to obtain a white solid. The white solid was recrystallized with glacial acetic acid and dried under vacuum to obtain propylmaleic anhydride.

4. The manufacturing process for the external 3PE and internal epoxy resin anti-corrosion pipe according to claim 3, characterized in that, The molar ratio of resin acid, 3-propylfuran-2,5-dione and p-toluenesulfonic acid is 1.8~2:1:0.1, and the mass-volume ratio of 3-propylfuran-2,5-dione to glacial acetic acid is 1g:2~2.5mL.

5. The manufacturing process for the external 3PE and internal epoxy resin anti-corrosion pipe according to claim 2, characterized in that, In step S11, the molar ratio of propylmaleic anhydride, pyridine, sulfoxide and N,N-dimethylformamide is 1:1:3:0.01; In step S12, 1 mmol of propylmaleic anhydride chloride is added to every 1 mL of tetrahydrofuran in reaction solution A; 1 mmol of 2-methylimidazole is added to every 1 mL of tetrahydrofuran in reaction solution B, and the molar ratio of 2-methylimidazole to triethylamine is 1:1; the volume ratio of reaction solution A to reaction solution B is 1:

1. In step S13, the extruder temperature is: 50~55℃ in zone 1, 90~95℃ in zone 2, and 70~75℃ in zone 3.

6. The manufacturing process for the external 3PE and internal epoxy resin anti-corrosion pipe according to claim 2, characterized in that, In step S13, the components of the epoxy powder coating, by weight percentage, are as follows: 55-65% bisphenol A type epoxy resin, 1-5% 2-methylimidazolium-propylmaleic anhydride, 30-38% filler, 1-1.5% leveling agent, 1-2% pigment, and 0.5-1% benzoin.

7. The manufacturing process for the external 3PE and internal epoxy resin anti-corrosion pipe according to claim 2, characterized in that, The preparation method of the silanized nanoparticle suspension is as follows: dodecyltrimethoxysiloxane is added to an ethanol-water mixture with a mass ratio of 9:1, and the mixture is stirred at 2000 r / min for 20-30 min at room temperature. Then, nano-alumina particles are added to the mixture, and the mixture is stirred for another 10-15 min to obtain a suspension. The suspension is then ultrasonically dispersed for 20 min to obtain the silanized nanoparticle suspension.

8. The manufacturing process for the external 3PE and internal epoxy resin anti-corrosion pipe according to claim 7, characterized in that, The mass ratio of the nano-alumina particles to dodecyltrimethoxysiloxane is 1:1.2, and the mass ratio of the dodecyltrimethoxysiloxane to the ethanol-water mixture is 1:

50.

9. The anti-corrosion pipe prepared by the production process of the external 3PE and internal epoxy resin anti-corrosion pipe according to claim 1.

Citation Information

Patent Citations

  • Technology for spraying epoxy powder inside and outside steel pipe

    CN107377337A

  • Large-caliber anti-corrosion steel tube and manufacturing process thereof

    CN109210282A

  • Production process of steel pipe coated with three PE layers and internally coated with epoxy

    CN113522705A

  • Solvent-free epoxy anticorrosive paint and preparation method thereof

    CN120775463A

  • Large-diameter anti-corrosion steel pipe

    CN209164783U

Cited By

  • High-temperature-resistant and cathodic disbonding-resistant 3PE anti-corrosion pipeline and preparation method thereof

    CN121821842A